Effectiveness of Interactive Animation Media in Improving Conceptual Understanding Physics Education at National High School of Tengku Sulaiman Malaysia - Khualid, Khadijah; Rohmah, Siti Noor (Lembaga Publikasi Ilmiah Nusantara, 2025)
This study aims to evaluate the effectiveness of interactive animation media in enhancing students’ conceptual understanding in physics education at the National High School of Tengku Sulaiman, Malaysia. The research was conducted using a quasi-experimental method with a pre-test and post-test control group design. A total of 60 students from two equivalent classes were selected as the sample, with one class receiving instruction through interactive animation media and the other through conventional teaching methods. The instrument used was a validated conceptual understanding test consisting of multiple-choice and open-ended questions tailored to the physics topics covered. Quantitative data analysis was conducted using descriptive statistics and inferential tests, including paired and independent samples t-tests. The results showed that students in the experimental group demonstrated significantly higher improvement in conceptual understanding compared to the control group. The use of interactive animations allowed students to visualize abstract concepts, engage in self-paced learning, and foster deeper cognitive connections. Furthermore, the media stimulated curiosity and motivation, leading to more active participation during lessons. These findings suggest that integrating interactive animation media into physics instruction can be a powerful pedagogical strategy to address students' learning difficulties and enhance academic outcomes. The study recommends broader implementation of such media in science classrooms and further research on its long-term impact.